Influence of calcium salts of long chain fatty acids on the intake and digestibility of rations in female kids under heat stress - Isabella Ribeiro Ferrari; Claudete Regina Alcalde; Ludmila Couto Gomes; Bruna Susan de Labio Molina; Orlando Rus Barbosa; Sérgio Mangano de Almeida Santos (Acta Scientiarum. Animal Sciences, 2016)
This study aimed to evaluate the effect of the addition of calcium salts of long chain fatty acids (CSFA) on the intake and digestibility of diets. Twenty-five female goat kids housed in digestibility cages and subjected to heat stress of 32°C in a climatic chamber, were used. The female kids were distributed in a randomized block design with five treatments: control (without inclusion of CSFA) and 6.25; 12.50; 18.75 and 25.00 g CSFA kg-1 of DM. The inclusion of CSFA in rations did not influence water intake (3.08 L day-1), dry matter (0.66 kg day-1), organic matter (0.62 kg day-1), crude protein (0.12 kg day-1), neutral detergent fiber (0.27 kg day-1) and total carbohydrate (0.47 kg day-1). The results of the digestibility of dry matter (0.66 kg kg-1), organic matter (0.67 kg kg-1), crude protein (0.78 kg kg-1), neutral detergent fiber (0.47 kg kg-1) and total carbohydrate (0.63 kg kg-1) were not affected by the treatments. However, there was a positive linear effect on the intake and digestibility of ether extract. Therefore, the addition of calcium salts of long chain fatty acids in the diets for female kids under heat stress of 32°C does not influence the intake and digestibility of dry matter and nutrients, except for ether extract, which is intrinsic to the product added to the rations.